Infective Endocardatis at the Yaounde General Hospital: Clinical aspects and outcome (Case Series) - Boombhi, Jérôme; Menanga, Alain; Hamadou, Bâ; Kingue, Samuel (Journal of Cardiovascular Medicine and Cardiology, 2017)
Introduction: Infectious endocarditis (IE) is a severe pathology. Its epidemiological, clinical and evolutive profile varies a lot depending if it is in the context of a developed country or developing country. In our context, very little data exists on the subject. Objectives: Describe the clinical aspects and outcome of IE in the Yaoundé general hospital. Methods: We carried out a descriptive retrospective study using clinical records of patients who had presented with IE in the cardiology unit of the Yaoundé general hospital from June of 2008 to May of 2013. Results: During this 5year period, 1846 patients were admitted in the cardiology unit and 10 of these cases were IE giving a hospital prevalence of 0.54%. The sex ratio was 1. The average age of the patients was 44.7 +/- 14.2 years. Rhumatismal valvulopathy was found as the most frequent predisposing factor, with 50% of the cases. The most frequent symptoms were fever and a heart murmur, which were found in 100% and 90% of the cases respectively. An inflammatory syndrome with anaemia was found in 90% of cases, leucocytosis with predominance of polymorphological neutrophils (PMN) in 80%, a raised ESR and CRP in all the patients. Hemocultures were positive only in 30% of the cases; however 60% of the patients had just one pair hemoculture done. Streptococcus was found in 2 cases and staphylococcus in 1 case. On echocardiography, vegetation and valvular regurgitation were found in all the patients. The antibiotherapy protocols were globally in conformity with recommendations and 40% of the patients completed their treatment. We found 4 deaths. Conclusion: IE is a rare pathology in our unit. Rhumatismal valvulopathy is the principal predisposing factor. Its management is limited by technical conditions and economic difficulties.